Analysis of PAUD Learning Model Beyond Centers and Circle Time (BCCT) and Its Implementation In Educational Institutions - Werdiningsih, Wilis; Rochmah, Elfi Yuliani (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
Early Childhood Education (PAUD) is an important stage for a child's growth. The selection of educational institutions with certain learning models, it is important for parents to consider before making a choice in one school. There are various kinds of PAUD learning models. Among these learning models are the classical model, the cooperative learning model, the center and circle time-based learning model (beyond centers and circle time/BCCT) and the area learning model (interest). Among these models, the center-based learning model and circle time are learning models that are still rarely applied in PAUD. This study aims to analyze the center-based learning model and circle time in terms of preparation and implementation. The approach used in this study is a qualitative approach. Data were obtained through interview, observation and various literature related to PAUD learning models. The results show that the center-based learning model and circle time is a learning model with four steps, namely the environmental footing, the footing before playing, the footing during playing and the footing after playing in the learning activities. The application of this learning model requires teachers to carry out preparatory activities every day. It is hoped that the aspects of children's development can improve through various series of activities in the central class which are followed by children alternately every day.